W zawieszeniu - Krzystek, Waldemar (Poland, 1987)
Anna, a nurse, meets her wartime lover Marcel in 1951. Learning that he has been sentenced to death for his role in the Home Army, she hides him in her cellar for five years. She becomes pregnant with his child and has the baby out of wedlock. Despite the hardships and gossip she holds out much better than he. In 1956 when the political climate changes, he resurfaces and is arrested, but then acquitted by the court.
Keywords: Fiction films